A review of industrial food processing using solar dryers with heat storage systems. (March 2023) - Ekka, Jasinta Poonam; Kumar, Dhananjay
Abstract: In the current scenario of food scarcity, most developing countries are facing the issue of food losses due to improper post-harvesting process, which accounts for about 50% of fruits and vegetables and 25% of food grains. Conventional dryers and cold storages are cost-intensive, and the rise in fossil fuel prices has intensified the problem. Cold storage is not accessible to farmers in remote locations. Solar drying is one of the primitives methods to reduce post-harvest losses. The use of solar-based drying systems is cost-effective for food drying. Using a solar dryer with a heat storage system eliminates the intermittent nature of solar radiation. Solar dryer integrated with thermal storage materials promotes a continuous drying process at a steady temperature of ∼50 °C for quality drying of food products. The thermal energy storage materials used in the dryer system store the thermal energy during sunshine hours and discharge it during the off-sunshine hours for drying applications. This paper aims to present state-of-the-art of solar thermal energy storage technologies for industrial food processing applications. Highlights: Due to the intermittent nature of solar energy, thermal storage-based solar dryers are preferable. Paper presents the latest trends of sensible and latent heat storage materials used in industrial drying process. Helps in improving the temperature homogeneity in the drying chamber for temperature-sensitive agricultural products. It reduces emissions post-harvest losses and GHGs emissions.